Steroid unresponsive case of ulcerative Mucha-habermann disease (Febrile Ulcernecrotic Mucha-Habermann disease) treated with methotrexate - Deepam J Shah; Rajeev Dhir; Harsh Shah; Naveen Chawla (Wolters Kluwer Medknow Publications, 2014)
A 20 year old male presented with fever associated with eruption of papules, plaques and vesiculobullous lesions on the chest, back, extremities, palms, soles, and genital mucosa of 20 days duration. Histopathological examination revealed epidermal clefts, edema and vacuolar degeneration of keratinocytes, basal cell degeneration, and dermal perivascular lymphocytic infiltrate. On the basis of clinical features and histology, a diagnosis of febrile ulceronecrotic Mucha-Habermann disease (FUMHD) was made. Treatment with doxycycline (100 mg BD for 4 weeks) and oral prednisolone 60 mg/day tapered to 25 mg in 4 weeks led to initial response that was followed by a relapse on tapering steroid. Addition of methotrexate (7.5 mg increased to 15 mg in 2 weeks) led to a dramatic response.